Propolis and its direct and indirect hypoglycemic effect - Mohamed T Al-Hariri (Wolters Kluwer Medknow Publications, 2011)
Propolis means a gum that is gathered by bees from various plants. It is strongly adhesive resinous substance, collected, transformed, and used by bees to seal holes in their honeycombs. Bees use it to seal holes in their honeycombs, smooth out internal walls, as well as to cover carcasses of intruders who died inside the hive in order to avoid their decomposition. Propolis also protects the colony from diseases because of its antiseptic efficacy and antimicrobial properties. It also has been reported to possess various biological activities, namely anticancer, antioxidant, anti-inflammatory, antibacterial, antifungal, and hypolipidemic. The aim of this review is to evaluate the hypoglycemic effect of propolis since a little number of researches studied this effect when we compare with the huge number of papers that reported many other biological activities.